THEOLOGICAL AND SPIRITUAL MEANING IN THE REPETITION OF THE WORD ALLAH IN SURAH AL-MUJADILAH - Anwar; Dian Erwanto (Adisam Publisher, 2026)
Surah Al-Mujadilah has a unique linguistic feature in the Quran, namely the consistent mention of the word Allah in every verse, a total of 40 times in 22 verses. This phenomenon invites attention for in-depth study, especially in its theological and spiritual aspects. This research uses a qualitative method with a thematic (maudhū‘ī) approach to Surah Al-Mujadilah, and the analysis is based on the classical interpretation of Ibn Jarir At-Thabari. The research findings indicate that the repetition of the word